Preoperative circulating peroxiredoxin 1 levels as a predictor of non-alcoholic fatty liver disease remission after laparoscopic bariatric surgery - Cheng, Xiaoyun; Fu, Zhibing; Xie, Wei; Zhu, Liyong; Meng, Jie (Frontiers in Endocrinology, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with obesity and insulin resistance and can be improved after bariatric surgery. Circulating Peroxiredoxin 1 (Prdx1) protein was reported to regulate energy metabolism and inflammation. This study aimed to investigate the roles of serum prdx1 in NAFLD patients with obesity undergoing LSG and to develop a prognostic model to predict the remission of severe NAFLD. Methods: The data of 93 participants from a tertiary hospital were assessed. Before laparoscopic sleeve gastrectomy (LSG) and three months after LSG, anthropometric parameters, laboratory biochemical data, and abdominal B-ultrasound results were collected, and their hepatic steatosis index (HSI) and triglyceride-glucose index (TyG) were calculated. A NAFLD improvement (NAFLD-I) nomogram prediction model was constructed using the least absolute shrinkage and selection operator (LASSO) regression and multiple regression, and its predictive ability was verified in a validation cohort. Results: The baseline Prdx1 (OR: 0.887, 95% CI: 0.816-0.963, p=0.004), preoperative TyG (OR: 8.207, 95% CI: 1.903-35.394, p=0.005) and HSI (OR: 0.861, 95% CI: 0.765-0.969, p=0.013) levels were independently associated with NAFLD-I at three months after LSG in NAFLD patients with obesity. In the primary and validation cohorts, the area under the receiver operating characteristic (AUC) of the developed nomogram model was 0.891 and 0.878, respectively. The preoperative circulating Prdx1 levels of NAFLD patients with obesity were significantly reduced after LSG (25.32 [18.99-30.88] vs. 23.34 [15.86-26.42], p=0.001). Prdx1 was related to obesity and hepatic steatosis based on correlation analysis. Conclusion: The nomogram based on preoperative serum prdx1, HSI and TyG could be an effective tool for predicting remission of severe NAFLD after LSG.